A Mousetrap for Carbenium Ions: NMR Detectives at Work. Issue 33 (26th June 2015) - Buntkowsky, Gerd; Gutmann, Torsten
<x xml:space="preserve">Abstract</x> The combined efforts of German and Chinese scientists applying solid‐state NMR spectroscopy, DFT calculations, and chemical modeling provided experimental proof of the tert‐butyl cation as a reaction intermediate in the butene/isobutene conversion on acidic zeolites.